2007
DOI: 10.1016/j.jvs.2006.11.010
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer testing to determine the duration of anticoagulation therapy

Abstract: women with sphingomyelin levels of Ն60 mg/dL than in women with sphingomyelin levels of Ͻ39 mg/dL. This association did not remain significant after multivariant adjustment for standard cardiovascular risk factors. Men with sphingomyelin levels of Ͼ60 mg/dL had higher calcium scores (135 vs 99 Agatston units, P ϭ .01) than men with sphingomyelin levels Ͻ39 mg/dL. Comment: Sphingomyelin accumulates in atheromas in animal models and in human atheroma. Much sphingomyelin found in arteries arises from synthesis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(125 citation statements)
references
References 0 publications
7
111
0
7
Order By: Relevance
“…In comparison with all previous studies on D-dimer in patients with a single VTE event [3][4][5]7], we observed a lower rate of patients with normal D-dimer at 30 days, a higher rate of recurrences in the first month of the study, and a slightly higher annual rate of VTE recurrences when comparing the groups of patients with negative D-dimer at 30 days.…”
supporting
confidence: 47%
See 1 more Smart Citation
“…In comparison with all previous studies on D-dimer in patients with a single VTE event [3][4][5]7], we observed a lower rate of patients with normal D-dimer at 30 days, a higher rate of recurrences in the first month of the study, and a slightly higher annual rate of VTE recurrences when comparing the groups of patients with negative D-dimer at 30 days.…”
supporting
confidence: 47%
“…The PROLONG study has previously evaluated the predictive role of Ddimer measurement after withholding VKA treatment in patients with a first episode of unprovoked VTE [5]. Patients with a positive D-dimer 1 month after the discontinuation of anticoagulation who were not restarted on VKA treatment had a significantly higher incidence of VTE recurrences than patients with a negative D-dimer (10.9 events per 100 patient/years and 4.4 events per 100 patient/years, respectively).…”
mentioning
confidence: 99%
“…RVT assessment is an easy method, does not seem to be influenced by the aforementioned conditions, but requires some expertise and is, to a certain extent, a subjective technique. A very important issue is the fact that these tools can identify patients carrying a low risk for recurrent VTE; these patients, in fact, may safely benefit from a short course (3 months) of VKA treatment [7][8][9]. Concerning RVT specifically, the absence of a residual clot is associated with a negligible risk for recurrent VTE; this may allow a short course of VKA in about one-third of the entire DVT patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, D-dimer (D-d) assay and residual vein thrombosis (RVT), detected by compression ultrasonography (C-US), have shown to be the most suitable methods for assessing the optimal duration of VKA administration. In fact, a number of studies have shown that negative results with these parameters after 3-6 months of therapy can identify a group of patients at low-risk for recurrent thrombosis in whom VKA treatment can be stopped [7][8][9][10]. However, these previous investigations have some limitations; first, in some trials, 30% of the patient population had provoked DVT [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation